A Biomechanical and Ease of Learning Comparison Study of Arthroscopic Sliding Knots - Teo, Seow Hui; Ng, Wuey Min; Al-Fayyadh, Mohamed Zubair Mohamed; Ali, Mohamed Razif Mohamed (Springer, 2020)
Introduction: This study aims to compare the biomechanical properties and ease of learning and tying of our novel knot (UM Knot) with other commonly used arthroscopic sliding knots. Materials and methods: The Duncan, HU, SMC, Pretzel, Nicky’s and square knots were selected for comparisons with UM knot. All knots were prepared with size 2 HiFi® suture by a single experienced surgeon and tested with cyclic loading and load to failure tests. The ease of learning was assessed objectively by recording the time to learn the first correct knot and the total number of knots completed in 5 min by surgeons and trainees. Results: The UM knot average failure load is significantly superior to the HU knot (p < 0.05) and comparable to Duncan, SMC, Pretzel and Nicky’s knots. According to the ease of learning assessment, UM, Duncan, SMC, Pretzel and Nicky’s knots took statistically less time to learn than the HU knot. Although not significant, the failure count due to slippage is fewer in UM knot compared with other knots. Conclusions: This study showed that UM knot is among the easiest knot to learn and tie, along with Duncan, SMC, Pretzel and Nicky’s knots. Their biomechanical properties are comparable and their loads to failure were superior to the HU knot. © 2020, Indian Orthopaedics Association.